2014
DOI: 10.1016/j.ijrobp.2014.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib Versus Radiation Therapy for Brain Metastases in Patients With EGFR-Mutant Lung Adenocarcinoma

Abstract: Purpose/Objectives Radiation therapy (RT) is the principal modality in the treatment of patients with brain metastases (BM). However, given the activity of EGFR tyrosine kinase inhibitors in the central nervous system (CNS), it is uncertain whether upfront brain RT is necessary for patients with EGFR-mutant lung adenocarcinoma with BM. Methods and Materials Patients with EGFR-mutant lung adenocarcinoma and newly diagnosed BM were identified. Results 222 patients were identified. Exclusion criteria included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 25 publications
4
61
2
2
Order By: Relevance
“…Better local control was found in both groups treated with upfront RT. In the WBRT group, the administration of erlotinib within 2 months of WBRT was associated with improved intracranial control on univariate analysis (23). A recent publication compared treatment outcomes between TKI monotherapy versus RT plus TKIs in a cohort of 133 patients with a diagnosis of stage IV NSCLC with brain metastasis, finding a better median intracranial PFS (16.0 vs. 11.5 months, p=0.017) and a better OS (22 vs. 15 months p=0.015) in the RT plus TKI group.…”
Section: Discussionmentioning
confidence: 99%
“…Better local control was found in both groups treated with upfront RT. In the WBRT group, the administration of erlotinib within 2 months of WBRT was associated with improved intracranial control on univariate analysis (23). A recent publication compared treatment outcomes between TKI monotherapy versus RT plus TKIs in a cohort of 133 patients with a diagnosis of stage IV NSCLC with brain metastasis, finding a better median intracranial PFS (16.0 vs. 11.5 months, p=0.017) and a better OS (22 vs. 15 months p=0.015) in the RT plus TKI group.…”
Section: Discussionmentioning
confidence: 99%
“…Stereotactic radiosurgery (SRS) and whole brain radiotherapy (WBRT) concomitantly or followed by EGFR-TKIs remain the current gold standard for patients with BM, even if they are often associated with considerable adverse neurotoxicity and questionable efficacy. Activity of upfront first-generation EGFR-TKIs has been reported in retrospective series including low number of EastAsian patients (Park et al, 2012;Iuchi et al, 2013;Gerber et al, 2014;Zhang et al, 2016a), overall showing poor response rates likely due to the low penetration of such agents across the bloodbrain barrier (BBB) (Zhao et al, 2013;de Vries et al, 2012). Some studies showed that erlotinib has a better central nervous system (CNS) penetration than gefitinib (Togashi et al, 2012), thus suggesting that it could be preferred if TKI monotherapy is used upfront for asymptomatic patients with BM.…”
Section: Activity Against Brain Metastasismentioning
confidence: 99%
“…Agents of this class can be used in first-line treatment of metastatic patients. Gerber et al found equivalent survival in lung cancer patients with brain metastases treated with upfront erlotinib versus standard-of-care whole-brain radiation therapy [55]. Although RTOG 0320 found a potentially deleterious effect to combination SRS and erlotinib, Welsh et al found no significant additional neurotoxicity in a phase II study that added erlotinib to whole brain RT.The overall response rate was 86%.…”
Section: Targeted Therapies For Breast Cancer Lung Cancer and Renalmentioning
confidence: 99%